Imperfect Acquisition of a Related Variety? Residual Clefting and What It Reveals about (Gradient) Bilectalism - Tsiplakou, Stavroula (Frontiers in Communication, 2017)
This paper explores the concept of gradient bilectalism by capitalizing on insights from recent developments in Second Language Acquisition, particularly the suggestion that aspects of the syntax-discourse interface that are not easily accessible to the learner may lead to fossilization, even at end state. I explore the implications of this suggestion for bilectal grammars by examining the ways in which speakers of Cypriot Greek do syntactic focusing in Standard Greek. The phenomenon is structurally different in the two varieties of Greek examined: clefting is the Cypriot syntactic focusing strategy par excellence while in Standard Greek the relevant strategy is movement of the focused item to an immediately preverbal position. Ιnterestingly, this focusing strategy is largely unattested in the acrolectal or standard-like production of bilectal Greek Cypriot speakers; on the contrary, the preferred strategy for syntactic focusing appears to be clefting, as is indicated by data from spontaneous speech. Quantitative data from a questionnaire survey presented in this paper confirm that such ‘residual clefting’ is all-pervasive even at end state, which in turn suggests imperfect acquisition of the relevant structural aspect of Standard Greek, the second variety of these otherwise bilectal speakers. The data invite an approach couched within the Interface Hypothesis and the argument is put forward that, being a structure at the interface between syntax and other modules or cognitive domains (semantics, pragmatics, discourse), focusing in the target variety is vulnerable as regards acquisition.